Optimization of Shell-side Single Phase Heat Transfer Correlation for Coil-wound LNG Heat Exchanger - Ji Peng; Li Yuxing; Zhu Jianlu; Wang Wuchang (Zhileng xuebao)
Shell-side thermodynamic calculation of coil-wound LNG heat exchanger is one of the important problems to be solved. Shell-side heat transfer models on low-temperature conditions are mentioned on very few occasions. It is a necessity to choose the best thermodynamic calculation correlation on cryogenic working conditions. The existing shell-side single phase heat transfer models were evaluated. Using the shell-side measurement data of coil-wound LNG heat exchanger on low-temperature conditions, this paper got the best shell-side heat transfer model for the pre-cooling stage of natural gas liquefaction process, and optimized this model. In conclusion, Abadzic heat transfer model gets the best accuracy and the strongest applicability, so it is properly selected for the pre-cooling stage of natural gas liquefaction process. The accuracy can be improved about 50% by the use of viscosity correction, the factor of which in the pre-cooling stage should be estimated at 1.05.